Proposição de um plano de gerenciamento de resíduos para instituição de ensino. Estudo de caso: Centro de Tecnologia da UFPB - João Pessoa -PB - Coutinho, Eugênio Côrte Real (2006)
The one elaboration plan of management of residues, with the knowledge of the diverse ones available alternatives for its application, supply subsidies the management e planning of the urban way, thus contributing for an improvement in the quality of life of the involved population, diminishing the impacts that come to be caused to the environment. The Federal University of Paraíba (UFPB) it generates the most diverse types of residues. However, the related institution does not possess a plan of management of residue e the same ones are handled, conditioned, collected, treated and/or made use of random form. The Center of Technology (CT) of the UFPB produces some residues as: chemistries, infections, papers, organic substance, among others e, as being an education institution, it must give the example of as to manage produced solid residues, in view of that these when they are badly managed they cause serious upheavals of sanitary, social order, economic e ambient. The objective of this work is to consider a plan of management of residues for the Center of Technology (CT), the Federal University of the Paraíba, situated in the city of João Pessoa. The used methodology it was the identification of the places of generation of the residues, application of questionnaires in the laboratories and workshops of the CT, the gravimetrical characterization of the deriving residues of the canteen and the presage during one year of the paper/cardboard produced in the CT. With relation to the residues produced in the CT it was observed that several are generated types of residues as: white paper, mixing paper and cardboard. The presage of these residues had beginning in the month of June of 2004 and ending in June of 2005. Also the existence of chemical and infections residues was detected, being that majority of the same ones is not conditioned, handled, collected, carried, treated and/or made use as the determination of Brazilian legislations (Resolutions of the National Advice of Environment - CONAMA and National Agency of Sanitary monitoring - ANVISA) and the Norms of Brazilian association of Norms Techniques - ABNT. The majority of the staff who it handles these residues did not have training and they do not use the equipment of individual protection - EPI's. The management plan of residues considered in this work it contemplates a set of action, with relation the collection, has carried, preservation and disposal of form to prevent any type of damage to the environment, respecting the peculiarities of the space physicist of a university campus